Pengembangan Media E-Book Bermuatan Kuliner Sasak pada Mata Pelajaran IPAS untuk Siswa Kelas IV di SDN 2 Dasan Tereng - Helma Urfiani; Moh. Irawan Zain; Ilham Handika (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This research is motivated by the prevalence of teacher-centered lecture methods and the heavy reliance on national textbooks, alongside the limited utilization of digital media and learning resources based on local wisdom. Furthermore, the lack of variety in instructional media has led to low student learning motivation. Addressing these issues, this study aims to develop a valid and practical educational e-book based on Sasak culinary heritage for Social and Natural Sciences (IPAS subject) instruction among fourth-grade students at SDN 2 Dasan Tereng. The methodology employed is Research and Development (R&D), following the ADDIE development model. Data collection techniques included interviews, observations, and questionnaires, using instruments such as interview guides, observation sheets, and validation scales for material experts, media experts, as well as teacher and student responses. Data analysis was conducted through validity and practicality tests using a 1–4 Likert scale. The results indicate that the developed e-book meets the criteria for being "highly valid" and "highly practical." Material expert validation achieved a score of 88.9% (highly valid), while media expert validation reached 92.7% (highly valid). Practicality testing showed a student response rate of 93% in small-group trials and 90.8% in large-group trials, with a teacher response rate of 91.9%, all categorized as highly practical. Consequently, the Sasak culinary-themed e-book is a viable contextual and interactive learning medium for fourth-grade elementary school students.